A Systematic Mapping Review of Software Usability Metrics - Murillo, Braulio; Pow-Sang, Jose (International Journal of Engineering and Technology, 2018)
The importance of usability in software applications is growing day by day, because it is increasingly the competitiveness of organizations to always offer better tools that meet the needs of their customers and users. However, there is no single instrument to measure the usability of software. There are several techniques to evaluate software usability, these evaluations being quantitative and qualitative. The main way to quantitatively evaluate a software product is by using software usability metrics. The present study performs a systematic mapping review to determine if there are experiences that use software usability metrics.Â Â Â